Investigation of the Solvent Extraction Using Alcohol and Water on Bryophylum pinnatum Leaves for Total Petroleum Hydrocarbon Degradation on Loamy Soil - Victor Chukwuemeka Ukpaka; Joy Chukwuemeka Peter Ukpaka; Abraham Peter Ukpaka; Ukpaka Chukwuemeka Peter (International Journal of Environmental Planning and Development Architecture, 2025)
Investigation of the solvent extraction using alcohol and water on Bryophylum pinnatum leaves for total petroleum hydrocarbon degradation on loamy soil was monitored for the purpose of evaluating the Micheal’s Menten functional parameters as well as the coefficients. The maximum specific rate of the total petroleum hydrocarbon (TPH), which was expressed as Vmax and the rate of the dissociation of the TPH, which is denoted as Km was computed in relationship to the effect of volume of solvent dosage. The performance of the two solvents used which is alcohol and water has demonstrated that both solvents are useful in the extraction of the necessary nutrients from the Bryophylum pinnatum leaves for crude oil remediation. The performance of the extracts obtained using the different solvent were rated good because of the high rate of the TPH reduction in concentration within 42 days.
Keywords: Bryophylum pinnatum; TPH; alcohol; investigation; leaves; solvent extraction; water